Late silurian marine shelly fauna of Central and Northern Vietnam - Tong-Dzuy, Thanh (Elsevier, 2019)
The Late Silurian (late Ludlow-Pridoli) brachiopods and bivalves from North and Central Vietnam are described and illustrated from the Kien An (North Vietnam) and My Duc (Central Vietnam) localities. The biostratigraphic relations and age of the fauna, the so-called Retziella fauna, are discussed. The My Duc fauna is the same as that at Kien An, indicating that during the Late Silurian both North Vietnam and Central Vietnam, situated on the South China and Indochina Plates respectively were probably fairly close geographically to each other. The Late Silurian is globally a time of moderately high, although not highest, provincialism as regards marine benthic invertebrates. A new brachiopod species, Nikiforovaena vietnamensisBoucot & Rong, and three new bivalve species Schizodus kienanensisFang, S. ? myducensisFang, and Modiomorpha paracryptaFang are described.